Novel high‐docosahexaenoic‐acid tuna oil supplementation modulates gut microbiota and alleviates obesity in high‐fat diet mice - Zhang, Jing; Yi, Congmin; Han, Jiaojiao; Ming, Tinghong; Zhou, Jun; Lu, Chenyang; Li, Ye; Su, Xiurong (Food science & nutrition, 2020)
Studies have documented the benefits of fish oil in different diseases because of its high n‐3 polyunsaturated fatty acid content. However, these studies mostly used commercially available fish oil supplements with a ratio of 18/12 for eicosapentaenoic acid and docosahexaenoic acid (DHA). However, increasing DHA content for this commonly used ratio might bring out a varied metabolic effect, which have remained unclear. Thus, in this study, a novel tuna oil (TO) was applied to investigate the effect of high‐DHA content on the alteration of the gut microbiota and obesity in high‐fat diet mice. The results suggest that high‐DHA TO (HDTO) supplementation notably ameliorates obesity and related lipid parameters and restores the expression of lipid metabolism‐related genes. The benefits of TOs were derived from their modification of the gut microbiota composition and structure in mice. A high‐fat diet triggered an increased Firmicutes/Bacteroidetes ratio that was remarkably restored by TOs. The number of obesity‐promoting bacteria—Desulfovibrio, Paraeggerthella, Terrisporobacter, Millionella, Lachnoclostridium, Anaerobacterium, and Ruminiclostridium—was dramatically reduced. Desulfovibrio desulfuricans, Alistipes putredinis, and Millionella massiliensis, three dysbiosis‐related species, were especially regulated by HDTO. Regarding the prevention of obesity, HDTO outperforms the normal TO. Intriguingly, HDTO feeding to HFD‐fed mice might alter the arginine and proline metabolism of intestinal microbiota. The high‐DHA tuna oil (TO) did produce different influence on the mice fed with high‐fat diet. The benefits of TOs were derived from their modification of the gut microbiota composition and structure in mice.